Analysis of Air Temperature Changes in East Nusa Tenggara Province Impacts of Climate Change for the Period 1971-2020 - Rafif Firjatullah; Hasibuan, Muhammad Ansori; Aditya Prapanca; Desak Putu Okta Veanti (Tinta Emas Institute, 2023)
This study aims to analyse temperature changes in NTT Province over the past 50 years, by comparing two periods, namely period I (1971-2000) and period II (1991-2020). Statistical analysis methods were used to examine temperature differences between the two periods, calculate the percentage of temperature change, and present time series graphs of average monthly temperatures. In addition, spatial analysis was conducted to investigate the seasonal temperature changes of December, January, February (DJF); March, April, May (MAM); June, July, August (JJA); and September, October, November (SON) regionally in NTT Province. Temperature data for 50 years was obtained from the European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis data, providing a strong basis for understanding the dynamics of temperature change with a high degree of accuracy. The results of this study show a steady increase in temperature in the 1991-2020 period by 0.894% compared to the 1971-2000 period, with a positive linear regression (0.0407), while the 1971-2000 period shows a less significant increase (0.0188). Spatial analysis shows a seasonal average temperature increase of 0.957°C in the 1991-2020 period. The findings on climate change characterised by temperature changes are expected to be the basis for more effective adaptation and mitigation policies in the face of climate change at the local level. This research is an important step in understanding the dynamics of climate change in vulnerable areas such as NTT Province.